Are Cactus Spines Modified Leaves? Morphological and Anatomical Characterization of Saguaro Seedlings (Carnegiea gigantea) with Special Focus on Aerial Organ Primordia - Cristina Betzabeth Miravel-Gabriel; Ryan Koeth; Nayelli Marsch-Martínez; Tania Hernández-Hernández (Plants)
The reduction of leaves was a key event in the evolution of the succulent syndrome in Cactaceae, evolving from large, photosynthetic leaves in Pereskia to nearly suppressed microscopic foliar buds in succulent Cactoideae. This leaf reduction was accompanied by the development of spines. Early histological studies, dating back a century, of the shoot apical meristem (SAM) in several species concluded that, in succulent cacti, axillary buds became areoles and leaves transformed into spines. However, these conclusions were based on limited observations, given the challenges of obtaining SAM samples from long-lived, often endangered species. Here, we present a complete study of early aerial organ development in seedlings of the iconic Carnegiea gigantea (saguaro), characterizing the different stages of seedling development. We focus on the SAM to track the emergence and development of primordia and aerial organs, closely following the spine development from undifferentiated structures. We demonstrate that young, few-days-old saguaro seedlings provide a valuable model for morpho-anatomical and molecular studies in Cactaceae. We also outline optimal laboratory practices for germinating saguaro seeds and conducting histological studies. Our observations confirm the absence of clear foliar structures and the presence of a distinct type of primordia, hypothesized to be foliar but lacking definitive foliar features. Based on our observations and a review of the literature, we revive the discussion on the ontogenetic origin of spines and propose saguaro seedlings as a promising model for studying the genetic identity of SAM primordia.